Effect of chemical passivation on corrosion behavior and ion release of a commercial chromium-cobalt alloy - Elnaz Moslehifard; Tahereh Ghaffari; Samineh Mohammadian-Navid; Mina Ghafari-Nia; Amirali Farmani; Farzad Nasirpouri (Tabriz University of Medical Sciences, 2020)
Background. Corrosion resistance and ion release of alloys play a crucial role in biomedical applications. The present study aimed to investigate an increase in corrosion resistance and reduction in ion release in a commercial Co-Cr-Mo alloy by the chemical passivation method. Methods. Based on ADA97, 20 samples of Flexicast alloy were cast, surface-polished, and electrolytically passivated at room temperature for 24 h in a sodium sulfate solution. Corrosion and ion release of the alloys before and after passivation were studied in normal saline solution. Corrosion resistance and the ion release rates were measured by the weight loss method and atomic absorption spectroscopy, respectively, before and after passivation after 1, 2, 3, and 4 weeks. The surface morphology of the samples was examined using scanning electron microscopy (SEM). The results were analyzed with Kruskal-Wallis and Mann-Whitney tests using SPSS 20 at a significance level of <0.05. Results. The corrosion rate in the passivated samples was significantly lower than the non-passivated samples at the intervals (1, 2, 3, and 4 weeks) (P<0.05). The passivation of the alloy significantly reduced Co and Cr ion release in the first and fourth weeks, and in the first, second, and fourth weeks, respectively (P<0.05). SEM images revealed localized pitting associated with the corrosion, which was less significant in passivated samples. Conclusion. Chemical passivation of the CR-Co alloy significantly reduced corrosion and ionic release of Cr and Co over time.